Avaliação da cinética e do equilíbrio de adsorção do corante disperso vermelho 60 utilizando β-ciclodextrina no tingimento de microfibra de poliamida com elastano - Ferreira, Bruna Thaisa Martins (2017)
In this work, the adsorption kinetic and equilibrium study of the disperse dye red 60 was carried out in the dyeing of knitted polyamide microfiber with elastane fabrics in order to evaluate the influence of β-cyclodextrin (β-CD) in substitution to the commercial levelling and dispersant Goldgen PES CONC in the dyeing. The undyed knitted polyamide microfiber with elastano fabrics were characterized by differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FTIR). The characterization of red 60 dye, the β-CD and the complexes of β-CD/red 60 was performed by FTIR spectroscopy. Dyeing experiments were performed to obtain the adsorption kinetic and equilibrium data at 80 °C in three conditions: (I) using β-CD/red 60 complex (II) using the commercial levelling and dispersant Goldgen PES CONC and (III) without the use of Goldgen PES CONC and β-CD. From the analysis of FTIR spectroscopy and DSC the knitted polyamide microfiber with elastane fabrics it could be characterized as polyamide type 6. In the FTIR spectroscopy analysis, changes were observed in the spectral bands that characterize the formation of the inclusion complex between β-CD and red 60 dye. The kinetic data of all the dyeing conditions studied were best fitted to the pseudo-second order model, the dyeing condition I presented kinetic rate comparable to the kinetic rate of the dyeing condition II. The adsorption equilibrium was reached in approximately 12 hours for dyeing condition I, 14 hours for condition II and 24 hours for condition III. It was determined that internal diffusion is the rate-limiting step of mass transfer in dyeing process studied. The samples dyed under dyeing conditions I, II and III did not show significant differences in total color difference, however, samples dyed in dyeing condition I in the presence of β-CD/red 60 complexes showed better color uniformity. The equilibrium data of all the dyeing conditions were best fitted to the BET isotherm model, suggesting the formation of multilayers. The dyeing performed in condition I at equilibrium concentrations (Ceq) higher than 300 mg L-1 of red 60 dye showed an increase in the amount of dye adsorbed on the fiber, indicating that in high dye concentrations the presence of β-CD increases the amount of solubilized dye and maintains the stability of the dye dispersion, being able satisfactorily used as substitute for the commercial leveling and dispersant agent Goldgen PES CONC.